Pencemaran Sungai: Analisis Peruntukan Undang-Undang di Bawah Akta Kualiti Alam Sekeliling 1974 (Kanun: Jurnal Undang-undang Malaysia, 2012)
This paper analyses the legal provisions relating to river pollution, in particular the Environmental Quality Act 1974 which is the parent Act in relation to the management and conservation of the environment. The scope of discussion focuses on the pollution caused by industrial factories. By using the method of interpretation of the statute, the analysis deliberates on the relevant express provisions that are directly related to river pollution The paper concludes by submitting proposals of improvement.Keywords: river, pollution, law, Environmental Quality Act 1974